Social Construction of Sharia Investment Among Millennial Muslims in Makassar: An Ethnographic Study - Amin, Andi Mustika (Journal Management & Economics Review (JUMPER), 2025)
This ethnographic study explores how millennial Muslims in Makassar construct their understanding and practice of Sharia-compliant investment through social processes and community interactions. Using participant observation, in-depth interviews, and focus group discussions with 32 participants across five investment communities, the research reveals three distinct pathways of knowledge construction: scholarly consultation, peer learning, and personal interpretation. The findings demonstrate that millennial Muslim investors actively negotiate religious principles with contemporary financial realities through collective deliberation processes, creating hybrid forms of "neo-Islamic finance" that integrate traditional religious compliance with environmental and social responsibility concerns. Technology plays a crucial role in facilitating communal investment practices, enabling participants to coordinate decisions through digital platforms while maintaining reverence for traditional religious authority. The study reveals that investment communities serve as sites of identity formation where participants construct modern Muslim professional identities that successfully integrate faith-based principles with material prosperity. The collective decision-making processes challenge the individualistic assumptions underlying conventional financial theory, demonstrating how peer networks serve as knowledge brokers in transforming abstract religious principles into practical investment criteria. These communities develop sophisticated screening practices and innovative investment structures, including informal investment pools that address both religious requirements and economic constraints. The research contributes to the understanding of contemporary Islamic finance practices and provides insights for developing culturally sensitive financial products and services tailored to millennial Muslim investors.